Melanoma in Organ Transplant Recipients: Incidence, Outcomes and Management Considerations - Faisal R. Ali; John T. Lear (Journal of Skin Cancer)
The incidence of melanoma continues to increase year on year. With better surgical techniques and medical management, greater numbers of organ transplants are being performed annually with much longer graft survival. The authors review our current understanding of the incidence of melanoma amongst organ transplant recipients, outcomes compared to the immunocompetent population, and management strategies in this burgeoning group.